2021
DOI: 10.1080/08998280.2021.1925827
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine for the treatment of childhood and adolescent psychiatric symptoms

Abstract: This retrospective study examined clinical parameters associated with amantadine treatment of psychiatric symptoms in children. A total of 297 pediatric patients were prescribed amantadine and met study criteria to assess clinical responses and medication outcomes. More than 62% of patients experienced clinically significant symptom control and 83% achieved at least maintenance symptom control, while 11% discontinued amantadine for nonresponse and 6% stopped amantadine because of side effects. Among patients p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…As with amantadine, early studies showed promise, either as a monotherapy 157 or in combination with risperidone, 158 but the quality of the evidence is low. Based on a retrospective cohort study conducted at Baylor University in Texas between 2014 and 2018 on 297 children ages 6–18 years with psychiatric disorders (ADHD being the most common 251/297), amantadine (median dose 200 mg daily) resulted in favorable clinical outcomes in 67.8% (40/59) of individuals with ASD, suggesting its benefits in individuals with ADHD comorbid with ASD 159 …”
Section: Future Directionsmentioning
confidence: 99%
“…As with amantadine, early studies showed promise, either as a monotherapy 157 or in combination with risperidone, 158 but the quality of the evidence is low. Based on a retrospective cohort study conducted at Baylor University in Texas between 2014 and 2018 on 297 children ages 6–18 years with psychiatric disorders (ADHD being the most common 251/297), amantadine (median dose 200 mg daily) resulted in favorable clinical outcomes in 67.8% (40/59) of individuals with ASD, suggesting its benefits in individuals with ADHD comorbid with ASD 159 …”
Section: Future Directionsmentioning
confidence: 99%
“…Один пациент в группе выбыл из исследования, и побочные эффекты были сопоставимы, за исключением снижения аппетита и беспокойства, которые имели более высокую частоту встречаемости при приеме метилфенидата. Эффективность обоих методов лечения была одинаковой в каждый момент времени с аналогичной тенденцией к снижению [50].…”
Section: препараты не зарегистрированные на территории рф по показани...unclassified